교정환자의 교정치료 특징이 구강건강관련 삶의 질(OHIP)에 미치는 영향 - 윤성욱(Sung-Uk Yoon); 오나래(Na-Rae Oh); 정미애(Mi-Ae Jeong) (한국콘텐츠학회 논문지, 14(3), 2014)
The purpose of this study was to promote effective health management of orthodontics patients by determining the effect that the factors related to orthodontics would have on the Oral Health Impact Profile (OHIP), and the subjects of this study was the local residents of Gangwon-do Province. The mean score of OHIP for the subjects was 2.97, while the mean score of physical factor was 3.01. The mean score of psychological factor was found to be 2.93. Thus, the orthodontics was found to have more influence on psychological factor. The item that had the greatest influence among the 10 items of Oral Health Impact Profile was found to be the question, "Have you ever felt shy due to your dental shape?" which had the mean score of 2.66. The characteristics that had significant effect on OHIP among general characteristics were found to be the age, religion, occupation, income, smoking or non-smoking status(p<0.05). In terms of the age, the age of 20 or less had the greatest effect with the mean score of 2.53. In relation to the occupation, the production/sales occupation had an influence with the mean score of 2.56 (p<0.05). Those with income exceeding KRW 4 million were found to have the mean score of 2.83 and 2.78. It turned out that the smokers had greater effect compared to the non-smokers in relation to the smoking/non-smoking status as the income was higher (p<0.05). The characteristics of orthodontics were manifested as the health perception in relation to Oral Health Impact Profile (OHIP) (p<0.05). Regarding the reason why they underwent the orthodontics, the 'uncomfortable feeling in chewing' was found to have the mean score of 2.69 and 2.67 (p<0.05). Regarding the orthodontics period, 1 to 2 years were found to have the mean score of 2.80 and 2.74, thus having an influence (p<0.05). In relation to the regret/non-regret over orthodontics, those who indicated that they regretted were found to have the mean score of 2.65 and 2.60 (p<0.05). Analysis of the relationship between Characteristics of orthodontic treatment and OHIP, orthodontic treatment reasons, oral health awareness, whether orthodontic treatment regret showed a statistically significant correlation. it is considered necessary to make constant efforts to help orthodontics patients, both physically and psychologically, in the course of treatment and improve their quality of lives. 본 연구는 교정치료 관련인자들이 구강건강영향지수(OHIP)에 주는 영향을 파악하여 교정환자의 효과적인 건강관리에 도움을 주고자 강원지역 주민을 대상으로 실시하였다. 대상자의 OHIP의 평균은 2.97이며 신체요인 평균은 3.01, 심리요인 평균은 2.93로 교정치료는 심리요인에 더욱 영향을 주며 구강건강영향지수 10항목 중 가장 영향을 많이 미치는 항목은 평균 2.66으로 '치아형태로 인해 창피한 적이 있었습니까'으로 조사되었다. 일반적인 특성 중 OHIP에 유의하게 영향을 준 특성은 연령, 종교, 직업, 수입, 흡연여부로 나타났다(p<0.05). 연령은 20대 이하가 2.53으로 영향을 가장 많이 주며 직업은 생산/판매직은 2.56으로 영향을 미치는 것으로 나타냈다(p<0.05). 수입은 400만원 초과가 2.83, 2.78로 수입이 많을수록, 흡연여부는 흡연자가 비흡연자에 비해 영향을 많이 미치며 것으로 조사되었다(p<0.05). 교정치료 특징이 구강건강영향지수(OHIP)에 건강인지도로 나타났다(p<0.05). 교정치료를 한 이유에서는 '저작 시 불편감'이 2.69, 2.67로 나타났다(p<0.05). 교정기간은 '1-2년'이 2.80, 2.74로 영향을 미치는 것으로 나타났다(p<0.05). 교정치료의 후회여부는 '후회한다'가 2.65, 2.60로 조사되었다(p<0.05). 교정치료의 특징과 OHIP의 상관관계를 분석한 결과 교정치료를 하는 이유, 구강건강인지도, 교정치료 후회여부가 통계적으로 유의하게 상관관계를 나타냈다. 이러한 결과를 바탕으로 교정환자의 신체적 정신적인 면에서 치료과정에 도움을 주고 또한 건강한 삶의 질 향상을 위하여 지속적인 노력이 필요하리라 사료된다.